German craftsmen of Saint Petersburg: specifics of formation and development of the community in the 18th – early 19th century - Shaidurov, Vladimir N. (Journal of the Belarusian State University. History, 2023)
During the imperial period, the German community of Saint Petersburg was not homogeneous. Not only the nobility, mostly from the Baltic Germans, played a prominent role in the urban life, but so did urban residents (burghers, tradespeople) and colonists, who dominated over crafts and agriculture industries. The object of study is the German crafts world in Saint Petersburg in the 18th – early 19th century, the subject being its formation and peculiarities of development. This topic is considered by the author of the article from the point of view of modernisation in the frontier territory. On the basis of various sources, the regulatory and legal framework for the formation and activity of German craft workshops has been determined. From various sources, the legislative framework of its formation and activity was deduced, which made it possible to determine the main trends of state policy regarding the community under study. The Charter on workshops at the end of the 18th century fixed the division of workshops in Saint Petersburg into Russian and foreign (predominantly German). The specifies of interaction between the urban Germans and the German colonists living in the colonies near the then-capital is described. The obtained statistical data enables us to talk about the close relationship of these population groups. The conducted research refutes the thesis about the isolation of the German colonists and proves their gradual integration into the urban environment of Saint Petersburg.
Keywords: Germans of Russia; Saint Petersburg colonies; German craft council; craftsman; workshop; identity; Saint Petersburg